2021
DOI: 10.1002/ccd.29496
|View full text |Cite|
|
Sign up to set email alerts
|

Comparing outcomes of general anesthesia and monitored anesthesia care during transcatheter aortic valve replacement: The Cleveland Clinic Foundation experience

Abstract: Background: Monitored anesthesia care (MAC) has become more widely used during transcatheter aortic valve replacement (TAVR) to avoid the complications of general anesthesia (GA). Methods:We included consecutive patients who underwent transfemoral-TAVR at our institution between January 2012 and April 2017. We compared outcomes with GA versus MAC.Results: Of 998 patients, MAC was used in 43.9%. MAC was associated with shorter

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Several studies have compared costs between MAC and GA in TAVR. 14,24,25,3234 This study demonstrated significant differences between anesthesia modalities in OR time, ICU LOS, and total LOS after propensity matching. It was hypothesized that these differences would translate to reductions in patient charges, but this was not the case.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Several studies have compared costs between MAC and GA in TAVR. 14,24,25,3234 This study demonstrated significant differences between anesthesia modalities in OR time, ICU LOS, and total LOS after propensity matching. It was hypothesized that these differences would translate to reductions in patient charges, but this was not the case.…”
Section: Discussionmentioning
confidence: 65%
“…Other comparisons of high-risk patients, confounded by baseline differences between groups, have demonstrated reduced OR, ICU, and total hospital LOS times with the use of MAC for TAVR. 32,34 With the inclusion of intermediate-risk and low-risk patients, the data presented herein offers more generalizability to the population currently treated with TAVR. Hospital and operator volume have been demonstrated to be associated with outcomes in TAVR.…”
Section: Discussionmentioning
confidence: 99%
“…34 Several studies have compared costs between MAC and GA in TAVR. 14,24,25,[35][36][37] This study demonstrated significant differences between anesthesia modalities in OR time, ICU LOS, and total LOS after propensitymatching. It was hypothesized that these differences would translate to reductions in patient charges, but this was not the case.…”
Section: Commentmentioning
confidence: 59%
“…Other comparisons of high-risk patients, confounded by baseline differences between groups, have demonstrated reduced OR, ICU, and total hospital LOS times with the use of MAC for TAVR. 35,37 With the inclusion of intermediate and low risk patients, the data presented herein offers more generalizability to the population currently treated with TAVR.…”
Section: Commentmentioning
confidence: 99%
“…MAC could lead to less haemodynamic instability due to the absence of stronger anaesthetic drugs such as those used in general anaesthesia. MAC has been shown to have similar to better safety outcomes than general anaesthesia with shorter hospital and intensive care unit length of stay 17 18…”
Section: Discussionmentioning
confidence: 99%